Comparison of N-acetylcysteine and cysteine in their ability to replenish intracellular cysteine by a specific fluorescent probe. Issue 60 (4th July 2016) - He, Xinyuan; Wu, Xiaofeng; Shi, Wen; Ma, Huimin
Abstract : NAC can increase the intracellular Cys level more effectively than Cys as revealed by a specific fluorescent probe. Abstract : A specific fluorescent probe, designed by a substitution-rearrangement mechanism, can discriminate cysteine from other thiols. Using this probe, N -acetylcysteine is revealed to be superior to cysteine to replenish intracellular cysteine in cells.